Cultural Analysis of Sweet Potato Farming for Food Development in Lamongan Regency, Indonesia - Emmy Hamidah; Bambang Heri Isnawan; Idum Satia Santi (Postgraduate, University of Mataram, 2024)
Sweet potatoes have an excellent opportunity to develop food consumption diversification programs based on local resources, carbohydrate sources, sources of various nutrients, industrial raw materials and animal feed, and different processed products. This study aims to analyze the development of food socially and culturally. The research was conducted using a survey method in Kalitengah District, Lamongan, Indonesia. Sampling was done purposively in 4 sweet potato center villages, with 165 farmer respondents. Data analysis uses descriptive analysis. The results of the study show that the age of sweet potato farmers is relatively old, an average of 53 years, while the education level of farmers is low, with 75.80% having a primary school education. 75.80% of farmers have over 30 years of experience cultivating sweet potatoes, and everything has been done culturally for generations. Farmers consume sweet potatoes that have not yet become a culture, which is 74.50%. A recommendation for valuable improvements is to train farmers on fertilizers and storage facilities. Efforts to develop sweet potato cultivation will be instrumental in policy making. In the future, it is hoped that the community will be able to improve the culture of consuming sweet potatoes.